Immigration et opinion publique : regards croisés sur l’immigration économique espagnole en France - Elodie Das Neves (Les Cahiers de Framespa)
Looking at the massive Spanish economic immigration during the « Trente Glorieuses » through the prism of public opinion leads us to analyse in turn how the inhabitants of the receiving country saw this phenomenon and how the immigrants saw the society which accommodated them. The analysis from a diachronic perspective opinion polls shows that using stereotypes, wavering between attraction and rejection and the progressive integration of Spanish people into French society are amongst the many elements which characterized the exchange of views between these people.